KELUARGA BERENCANA (KB) PERSPEKTIF Al-QUR’AN - Maskanah Maskanah (CV. Adiba Aisha Amira, 2024)
According to Islamic concepts, family is a united relationship between men and women through a marriage contract according to Islamic teachings. Mahmud Syaltut defines family planning as the regulation and spacing of births or efforts to prevent pregnancy temporarily or even permanently in connection with certain situations and conditions, both for the family concerned and in the interests of society and the state. Based on the Al-Qur'an, which is the main source of Islamic law, no Sharia text prohibits or orders family planning. This must be returned to the rules of Islamic law which state: